Discovery of Post-Translational Modifications in Emiliania huxleyi - Van-An Duong; Onyou Nam; EonSeon Jin; Jong-Moon Park; Hookeun Lee (Molecules, 2021)
Emiliania huxleyi is a cosmopolitan coccolithophore that plays an essential role in global carbon and sulfur cycling, and contributes to marine cloud formation and climate regulation. Previously, the proteomic profile of Emiliania huxleyi was investigated using a three-dimensional separation strategy combined with liquid chromatography-tandem mass spectrometry (LC-MS/MS). The current study reuses the MS/MS spectra obtained, for the global discovery of post-translational modifications (PTMs) in this species without specific enrichment methods. Twenty-five different PTM types were examined using Trans-Proteomic Pipeline (Comet and PeptideProphet). Overall, 13,483 PTMs were identified in 7421 proteins. Methylation was the most frequent PTM with more than 2800 modified sites, and lysine was the most frequently modified amino acid with more than 4000 PTMs. The number of proteins identified increased by 22.5% to 18,780 after performing the PTM search. Compared to intact peptides, the intensities of some modified peptides were superior or equivalent. The intensities of some proteins increased dramatically after the PTM search. Gene ontology analysis revealed that protein persulfidation was related to photosynthesis in Emiliania huxleyi. Additionally, various membrane proteins were found to be phosphorylated. Thus, our global PTM discovery platform provides an overview of PTMs in the species and prompts further studies to uncover their biological functions. The combination of a three-dimensional separation method with global PTM search is a promising approach for the identification and discovery of PTMs in other species.